An examination of numerical portability in mobile communication in Uruguay - Néstor Gandelman; Flavia Roldán; Sofía Viera (Inter-American Development Bank (IDB), 2025)
This paper examines the effects of the introduction of mobile number portability (MNP) using data from Uruguay. MNP allows customers to switch mobile providers while retaining their phone number, thereby reducing switching costs and potentially enhancing competition. Our analysis reveals that firms responded by increasing the share of postpaid contracts, partially countering the exogenous reduction in switching costs with new endogenous barriers. We find that while market concentration increased in terms of subscriber share, it decreased for data traffic, reflecting differing customer behaviors and firms' commercial strategies. Additionally, we observed reductions in mobile data prices and an increase in new mobile subscribers, suggesting that MNP contributed to overall market growth. Using a world panel of data prices for the internet we find that MNP is associated with lower prices in the range of 42-50 percent.
Keywords: L96; L51; D43; 330; Mobile number portability; Telecommunications; Competition; Switching costs; Uruguay